Analisis pengaruh Discovery Learning terhadap Literasi Sains pada mata pembelajaran IPAS di Sekolah Dasar - Darsi, Darsi; Mansur, Mansur; Setyaningrum, Vidya (Borobudur Educational Review, 2025)
The low science literacy of Indonesian students in international studies like PISA indicates the need for more contextual learning. One approach that can be used is discovery learning, which is a learning model that encourages students to discover concepts thru direct experience. This study aims to: (1) describe students' scientific literacy in control and experimental classes, (2) examine the implementation of discovery learning, and (3) determine its effect on scientific literacy in the human digestive system material. The research uses a quantitative approach with a quasi-experimental pre-test-post-test control group design. The population consists of all fifth-grade students at SDN 68 Pontianak Barat. Class VB serves as the control group and Class VC serves as the experimental group, which were selected purposively. Data was collected thru tests, observations, and documentation. This is done using tools such as multiple-choice questions, observation checklists, and supporting documents. Gregory (V = 1.0) was used to test the validity of the instrument, and the non-parametric Mann-Whitney test was used for data analysis. The research results show: (1) The average science literacy of the control class increased from 40.20 to 59.65; (2) The experimental class increased from 42.45 to 65.00; (3) The implementation of discovery learning went well (100% completed); (4) The Mann-Whitney test showed a significance of 0.007 < 0.05 and an effect size of 0.42 (moderate category). In conclusion, the discovery learning model has a positive effect on improving students' scientific literacy, although the effect is not high